Nonsurgical Management of Apical Root Perforation Using Mineral Trioxide Aggregate - Omar Alzahrani; Faisal Alghamdi (Case Reports in Dentistry)
This study illustrates a conservative approach to nonsurgical management of apical root perforation in maxillary first molars. A patient was referred for retreatment of a maxillary left first molar. Her chief complaint was dull pain while biting in her maxillary left first molar. Periapical radiography showed radiolucency related to the mesiobuccal root and overextended gutta-percha through a perforation in the apical part of the distobuccal root. A CBCT scan was acquired and revealed the location and size of the apical perforation. The clinical examination showed that the tooth has been endodontically treated and the canals were filled, tender to percussion and palpation. Thus, the nonsurgical root canal retreatment was done and the perforation site was repaired by using mineral trioxide aggregate (MTA). At the one-year follow-up, after the management of apical root perforation, we observed periapical tissue healing and no pain due to percussion and palpation, without any clinical/radiological signs or symptoms. The prognosis of this case has a higher success rate with the development of new materials such as MTA. The MTA not only can seal the site of the perforation but also has the ability to induce calcification. Many factors can contribute to the success rate of perforated cases, including time, size, and location of the perforation. With the use of this material and good tools like a microscope, there are those with having higher chances of repair and eventually higher success rates.